2018
DOI: 10.1108/srj-04-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

Total quality management, corporate social responsibility and entrepreneurial orientation in the hotel industry

Abstract: Purpose The purpose of this paper is to examine how total quality management (TQM) and corporate social responsibility (CSR) affect entrepreneurial orientation (EO) in the context of the hotel industry. Design/methodology/approach Drawing from the hospitality literature, the relationships among TQM, CSR and EO were hypothesized and tested. Based on the valid responses collected from a survey questionnaire, structural equation modeling approach was used to examine the research model. Findings The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 61 publications
0
52
1
7
Order By: Relevance
“…Namely, only sustainable category R&D (impliedly via the digitalization) and the expansion of the pool of stakeholders (expressly via new customers) are mentioned in this respected. Therefore, well-established and reported link between CSR and total quality management from hotel industry in other jurisdictions (Jalilvand et al , 2018) is not confirmed by this Czech case study. Further, this study indicates that the potential of sustainable brand co-creation is much less developed in Czech hotel industry than in other jurisdictions, see highly developed and digitalized Asian countries (Chung and Byrom, 2020).…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Namely, only sustainable category R&D (impliedly via the digitalization) and the expansion of the pool of stakeholders (expressly via new customers) are mentioned in this respected. Therefore, well-established and reported link between CSR and total quality management from hotel industry in other jurisdictions (Jalilvand et al , 2018) is not confirmed by this Czech case study. Further, this study indicates that the potential of sustainable brand co-creation is much less developed in Czech hotel industry than in other jurisdictions, see highly developed and digitalized Asian countries (Chung and Byrom, 2020).…”
Section: Resultscontrasting
confidence: 69%
“…These challenges and their addressing involve basically each and every internal stakeholder. Especially the role of employees and their (un)readiness to reconcile the brand co-creation with these challenges (Chung and Byrom, 2020) and to go even more vigorously for mutually supported CSR and total quality management in the hotel industry is pivotal (Jalilvand et al , 2018). As well the growing role of the impact of social enterprises, including those from the hotel industry, on the economy in the Czech Republic needs to be appreciated (Tausl Prochazkova and Noskova, 2020).…”
Section: Overview Of the Literature Legislative And Analytical Frameworkmentioning
confidence: 99%
“…When embedded within strategic decision-making, EO plays an important role in firms' developing, commercializing and aggressively pursuing new products and service development and anticipating and responding to contingencies ( Hernández-Perlines, 2016 ; Rauch et al, 2009 ). EO is underpinned by distinct strategic orientation which collectively enhances business outcomes by creating new knowledge required for establishing new capabilities and re-energizing existing resources and capabilities, fostering an innovative mindset within the firm under differing turbulent and competitive environments ( Cavusgil and Knight, 2015 ; Jalilvand et al, 2018 ; Martin and Javalgi, 2016 ; Taheri et al, 2019 ). Arguably, a business with a strong EO focuses on gaining a superior performance by building a value-creating strategy which other competitors are unable to duplicate the benefits, or find it too costly to imitate.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…EO defines a way in which entities can differentiate themselves from one another [14], consolidating their sustainability practices in the short-, medium-, and long-term. Those entities with high EO develop a clear strategic orientation towards the integration of new knowledge, skills, and entrepreneurial abilities that creates a competitive advantage over their competitors [15]. The main objective of any organisation is to guarantee its sustainability and survival; providing added value through entrepreneurial initiatives is a fundamental element in achieving this.…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%